Volume 2B: Turbomachinery 2018
DOI: 10.1115/gt2018-75062
|View full text |Cite
|
Sign up to set email alerts
|

Study of Combustion Noise Generation in a Realistic Turbine Stage Configuration

Abstract: Generation of combustion noise is here studied in a realistic turbine stage configuration, where the temperature fluctuations generated by an aeronautical burner (responsible of the direct combustion noise generation, often neglected in most of the studies) are modelled using a cylindrical fluctuating energy source term placed upstream of the inlet guide vanes. This modelling not only better accounts for the actual physical combustion noise generation phenomena, but also for the actual stratification of temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This showed that the increase is partially due to the entropy generation of a shock wave and the wake. However, the magnitude of the generated entropy wave is of three magnitudes smaller [18] in comparison to the forced entropy wave in Fig. 9.…”
Section: A Entropy Wave Convectionmentioning
confidence: 68%
See 2 more Smart Citations
“…This showed that the increase is partially due to the entropy generation of a shock wave and the wake. However, the magnitude of the generated entropy wave is of three magnitudes smaller [18] in comparison to the forced entropy wave in Fig. 9.…”
Section: A Entropy Wave Convectionmentioning
confidence: 68%
“…9. An increase in axial entropy wave amplitude in the wake has been highlighted by Beceril et al [18]. This showed that the increase is partially due to the entropy generation of a shock wave and the wake.…”
Section: A Entropy Wave Convectionmentioning
confidence: 79%
See 1 more Smart Citation
“…Yet, the additional entropy source placed in front of the stator leading edge triggers a significant increase of the gradient of density on the suction side of the stator, and consequently the boundary layer flow with earlier transition, thicker and more unsteady vortex shedding impacting the rotor blades. Several outstanding findings have been made by Becerril et al [92], which are summarized by the entropy transmission coefficients shown in Figure 16. In both plots CHORUS (thick black line) stands for the 2-D stage predictions at midspan as presented by Papadogiannis et al [88], and studied in detail by Bauerheim et al [91].…”
Section: Resultsmentioning
confidence: 94%
“…The former result suggested that the actual reflection at the turbine inlet was less prone to instabilities, and the latter suggested that the 2-D approximation of CHORUS through the turbine stages could be satisfactory. More recently a more realistic cylindrical source term mimicking the actual temperature stratification and hot streaks at the exit of the combustion chamber in an actual aero-engine has been injected at the inlet in front of the stator leading edge [92]. The flow topology of both cases with and without entropy volumic spot are shown in Figure 15 for the latter case.…”
Section: Resultsmentioning
confidence: 99%